New regionalism theory—Indonesia’s rural development through a tourism perspective - Abu Bakar, Norlaila; Salleh, Norlida Hanim Mohd; Saukani, Mohd Nasir Mohd; Wijijayanti, Trisetia (Journal of Infrastructure, Policy and Development, 2025)
In an effort to bridge the gap of economic and social inequality among the community, rural areas in Indonesia are encouraged to be self-sufficient in generating income. This makes the central government create various policies so that the regional government maximizes the management of its potential as an economic resource for the well-being of its people. One of the ways to manage this potential is to encourage rural areas to create tourism products that can be sold to the public. The Indonesian governments openly use the tourism sector as a tool for the development in many rural areas. Next, efforts to achieve successful development of the district will be closely related to the strategic planning and long-term cooperation of each local government with stakeholders in its implementation. These two points are the basic elements of the new regionalism theory. This theory states that the role of local governments is very important in initiating and making policies for new economic activities for a significant improvement in the quality of their population. Therefore, this study tries to explore how the new theory of regionalism can include rural development from a tourism perspective as a way to stimulate the fading economy in rural area of Indonesia. The study found that the new theory of regionalism needs support from various aspects such as social-cultural, community participation, the three pillars of sustainable development namely economic, social, and environmental as well as basic aspects to shape sustainable rural development through tourism.